Pengenalan Pertanian Modern pada Siswa SMA 1 Godean melalui Pelatihan Kultur Jaringan Tanaman: Introduction to Modern Agriculture for SMA 1 Godean Students through Plant Tissue Culture Training - Rineksane, Innaka Ageng; Handayani, Etty; Sari, Supriyatin Kartika; Wulandari, Rani Agustina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
SMA Negeri 1 Godean, Sleman, Yogyakarta, has achieved significant academic success, including higher graduation rates and a consistent ranking among the top five high schools in Sleman Regency. This institution is recognized for its students' adherence to established rules and regulations. Consequently, the school aims to enhance its students' understanding by including agriculture, in partnership with the Faculty of Agriculture at Universitas Muhammadiyah Yogyakarta. SMA Negeri 1 Godean is equipped with Biology and Chemistry laboratories, along with a greenhouse, to facilitate the introduction and exploration of scientific disciplines. However, the institution lacks the facilities to implement modern agricultural techniques for its students. A modern agrarian approach is the plant tissue culture technology. The challenge at present is that the students of SMA Negeri 1 Godean lack an understanding of agriculture, both in general and in its modern form, and have not had practical experience with plant tissue culture. This service aims to familiarize SMA Negeri 1 Godean students with the science of agriculture and modern agricultural techniques through tissue culture. Efforts to address the partner's issues were implemented through various methods, including general and modern agricultural education, specifically plant tissue culture techniques; practical training in tissue culture methods; the acclimatization of Cavendish bananas; and evaluation. The results of the activities indicate an improvement in students' knowledge and skills following their participation in general and modern agricultural culture, especially in plant tissue culture techniques.